Induction of IL-9 in Peripheral Lymphocytes of Rheumatoid Arthritis Patients and Healthy Donors by Th17-Inducing Cytokine Conditions - Heim, Jana; Almanzar, Giovanni; Schmalzing, Marc; Gernert, Michael; Tony, Hans-Peter; Prelog, Martina (Frontiers in Immunology, 2021)
IL-9-producing Th9 cells display a group of helper T cells with similarities to Th17 and Th2 T cells and have been shown to be involved in synovial inflammation in rheumatoid arthritis (RA) patients. So far, it is unclear which parameters drive Th9 differentiation in lymphocytes derived from RA patients compared to immunologically healthy individuals and whether autocrine mechanisms are able to enhance Th9 polarization. Further, parallel pathways of induction of IL-17-producing cells with Th9 phenotype have to be distinguished from exclusively Th9-inductive mechanisms. Thus, the present study aimed to determine the parameters of Th9 induction by simulation in a standardized inflammatory cytokine milieu. Peripheral naive and non-naive T cells of RA patients and healthy donors (HD) were cultured under Th9 and Th17-driving conditions and phenotypically analyzed by flow cytometry and molecular analysis. Our findings indicate a similar differentiation pathway of Th9 and Th17 cells and similar distributions of IL-9+ T cells in RA and HD regardless of Th9- or Th17-promoting cytokine milieus. However, the induction of IL-9+ CD4+ T cells was more pronounced in HD than in RA. Similarly, IL-17+ CD4+ T cells were significantly stimulated by Th17-inducing conditions in HD. In conclusion, the results indicate that Th9- and Th17-inducing cytokine conditions mimicking autoimmune inflammation in RA may have similar stimulatory effects regarding polarization of peripheral naive and non-naive T cells into Th9 or Th17 cells. The results suggest that a well-balanced cytokine cocktail is needed to allow a distinguished differentiation into either Th9 or Th17 cells.